Guest editorial—Policies and practices in action to address soil erosion: A special issue from the Global Symposium on Soil Erosion 2019. (22nd July 2021) - Lefèvre, Clara; Balks, Megan; Nziguheba, Generose; Poch, Rosa M.
Abstract: This special issue is the second one drawn from the Global Symposium on Soil Erosion (GSER, May 15–17, 2019, Rome, Italy) and includes contributions dealing with the second theme of the GSER: Policies and practices in action to address soil erosion . While there is a good scientific understanding of the physical measures that can be used to prevent or mitigate soil erosion, the main constraints to progress often relate to policy development and or implementation as well as socio‐economic aspects that provide limitations to the implementation of sustainable soil management (SSM) practices including those directed to control erosion. There are no right or wrong answers to which policy or approach is most effective. Some combination of approaches needs to be adopted that work in the particular political, cultural, and socio‐economic environment under consideration. The papers included in this special issue provide examples, from the national to a local level that could be adapted, or used, to improve uptake and implementation of SSM practices to prevent or reduce soil erosion. Regardless of what policy or plan is developed, there has to be effective interaction with the local farmers and land managers as they are the key to implementing any actions that will make a practical difference on the ground. Effective policies cannot be developed or implemented without bringing the land managers 'on board' and the needs and limitations of the local farmers must be thoroughly understood and considered in any policy or plan development.